PENETUAN KADAR ZAT AKTIF PADA FLUOCINOLONE ACETONIDE CREAM DENGAN METODE SPEKTROFOTOMETRI UV- VIS - Risma Sari; Khairul Fuad (Politeknik ATI Padang, 2022)
Fluocinolone Acetonide Cream is a topical medication used to treat itching, redness, dry skin, crusting, inflammation, and discomfort of various skin conditions. This research was conducted to determine the levels of the active substance contained in Fluocinolone Acetonide Cream. Testing the levels of active substances is carried out to ensure the levels of active substances are in accordance with predetermined requirements. The side effect of the active substance is that if the drug has excess levels of the active substance it will endanger the drug user and if there is a deficiency of the active substance, the drug will not have any reaction. at a wavelength of 200-300 nm and the maximum wavelength of the Fluocinolone Acetonide Cream test is 238. The test results for determining the levels of active substances in the sample are 98.99% and 99.14% where the specifications used are between 90% - 110%. These results indicate that the sample levels fall within the specifications established by Pharmacopoeia edition I and II 2009.